Digital differential analysers - Shileiko, A. V. (Aleksei Voldemarovich) (International series of monographs on electronics and instrumentation, 1964)
Digital Differential Analysers presents the principles, operations, design, and applications of digital differential analyzers, a machine with the ability to present initial quantities and the possibility of dividing them into separate functional units performing a number of basic mathematical operations.